Prinsip Hukum Islam Terhadap Investasi Berbasis Pasar Modal: Upaya Menghindari Spekulasi dan Maisir Dalam Ekonomi Syariah - Ghaizka Figo Alfaeza; Evan Yusuf Priyokusumo; M. Aldeon Putra Adi Surya; Edho Setyawan; Alif Budhi Santosa; Bella Nova Silvia; Diana Setiawati (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The Islamic capital market in Indonesia has experienced rapid growth in line with the increasing awareness among Muslims of the importance of investing according to Islamic principles. As part of the national financial system, the Islamic capital market introduces instruments such as Islamic stocks, sukuk, and sharia mutual funds based on the values of justice, transparency, and the prohibition of riba (usury), gharar (uncertainty), and maysir (speculation or gambling). However, challenges remain in ensuring that all investment activities fully comply with sharia principles and are free from speculative elements commonly found in conventional markets. This study aims to examine: (1) how Islamic law regulates investment activities in the Islamic capital market, and (2) the fundamental differences between the Islamic and conventional capital markets in terms of legal principles, instruments, and economic objectives. The research employs a juridical-normative method with a qualitative approach, drawing on legal literature, fatwas issued by the National Sharia Council (DSN-MUI), and relevant capital market regulations in Indonesia. A descriptive analysis is used to assess the implementation of sharia principles in investment practices. The results indicate that the Islamic capital market emphasizes justice, transparency, and social welfare, while the conventional capital market prioritizes financial profit. In conclusion, the Islamic capital market serves not only as a halal investment platform but also as a reflection of an ethical, just, and sustainable Islamic economic system